FIKIH SIYASAH DAN PEMISAHAN KEKUASAAN: MENGANALISIS KETERKAITAN ANTARA HUKUM ISLAM DAN STRUKTUR PEMERINTAHAN MODERN - Akhmad Zaki Yamani (CV. ADIBA AISHA AMIRA, 2025)
This study examines the integration of Fikih Siyasah values with the principle of separation of powers in the context of modern governance. A qualitative approach was employed through literature review and comparative analysis, aiming to identify the similarities and differences between the two systems as well as the potential synergy that can enhance effectiveness, justice, and accountability in governmental administration. The findings indicate that although Fikih Siyasah and the system of separation of powers stem from different historical and philosophical frameworks, there is an overlap in values—such as justice, consultation, and oversight—that serves as a foundation for adapting Islamic values into modern control mechanisms. The theoretical and practical implications of this research contribute to the development of Islamic legal theory and open opportunities for governance structure reform, particularly in addressing the challenges of legal pluralism and the dynamics of globalization.